2014
DOI: 10.1016/j.ijheatmasstransfer.2013.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Manifold microchannel heat sink design using optimization under uncertainty

Abstract: A three-dimensional numerical model is developed and validated to study the effect of geometric parameters such as microchannel depth and width, manifold depth, and manifold inlet and outlet lengths on the performance of a manifold microchannel (MMC) heat sink. The manifold arrangement used to distribute the flow through alternating inlet and outlet pairs greatly reduces the pressure drop incurred in conventional fluid supply arrangements due to its shorter flow paths, while simultaneously enhancing the heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(23 citation statements)
references
References 22 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…The plenum interface plate is designed to have equal total inlet and outlet flow areas. Previous designs in the literature that were optimized for single-phase flows found the optimal inlet-to-outlet area ratio to be approximately 1.5:1 to 3.5:1 [29,32]; an increased outlet plenum size was incorporated in the current design to limit contraction of the high-velocity two-phase mixture at the channel outlet. One side of the plenum plate is mated to a 10 μm-thick double-sided adhesive and brought into contact with the manifold; the opposite side of the plenum plate is bonded to the microchannel plate ( Figure 2).…”
Section: Test Vehicle Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The plenum interface plate is designed to have equal total inlet and outlet flow areas. Previous designs in the literature that were optimized for single-phase flows found the optimal inlet-to-outlet area ratio to be approximately 1.5:1 to 3.5:1 [29,32]; an increased outlet plenum size was incorporated in the current design to limit contraction of the high-velocity two-phase mixture at the channel outlet. One side of the plenum plate is mated to a 10 μm-thick double-sided adhesive and brought into contact with the manifold; the opposite side of the plenum plate is bonded to the microchannel plate ( Figure 2).…”
Section: Test Vehicle Designmentioning
confidence: 99%
“…A variety of researchers have conducted numerical studies to identify optimized geometries and operating conditions for both the fluid distribution manifold and microchannel heat sink [28][29][30][31][32]. These studies concluded that 1) at a fixed pumping power, there is an optimal channel height, channel width, and flow length for which thermal resistance is minimized, 2) the flow length should be minimized to minimize pressure drop for a fixed heat flux until manifold pressure drop governs the overall pressure drop at extremely short flow lengths, and 3) decreasing the channel width and increasing the flow rate both increase the heat transfer rate at the cost of increased pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…5c presents the temperature profiles of the models with channel lengths of 1 mm, 3 mm and 5 mm for both base-lines 1 and 2. The results show that the bottom wall temperatures of the models with a shorter channel length were lower and more uniform than those for longer channels [26,27]. More specifically, with a channel length of 1 mm, the differences between the maximum and minimum temperatures on the bottom wall were 2.39°C and 2.56°C for the MN-MCHS with base-lines 1 and 2, respectively.…”
Section: A Channel Length Examinationmentioning
confidence: 84%
“…In 2012, Boteler et al [26] were first to propose the concept of a manifold microchannel heat sink (M-MCHS). Following that proposition, the investigations on the M-MCHS were continued by other groups of authors [27][28][29]. They reported that the M-MCHS could significantly reduce the pressure drop and improve the temperature uniformity on the bottom wall due to the truncation of the path of the coolant.…”
Section: Introductionmentioning
confidence: 99%
“…There are commonly two types of uncertainties: aleatory and epistemic [29,30]. Aleatory uncertainties are associated with physical variability (e.g., material properties, operating condition manufacturing, and tolerance) in the system and environment which are typically handled using probabilistic methods.…”
Section: Stochastic Analysis Methodsmentioning
confidence: 99%